2021
DOI: 10.3390/biomedicines9020185
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plaque Characteristics and Inflammation Using Magnetic Resonance Imaging

Abstract: Atherosclerosis is an inflammatory disease of large and medium-sized arteries, characterized by the growth of atherosclerotic lesions (plaques). These plaques often develop at inner curvatures of arteries, branchpoints, and bifurcations, where the endothelial wall shear stress is low and oscillatory. In conjunction with other processes such as lipid deposition, biomechanical factors lead to local vascular inflammation and plaque growth. There is also evidence that low and oscillatory shear stress contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 159 publications
(116 reference statements)
0
9
0
Order By: Relevance
“…In a multicenter prospective cohort study of patients with carotid stenosis and recent stroke/transient ischemic attack, Kelly et al showed that plaque inflammation associated 18 F-FDG uptake independently predicted future recurrent stroke after PET ( 33 ). Similarly, in a PET study using 18 F-fluorcholine ( 18 F-FCH), histological analysis of carotid endarterectomy specimens revealed a strong correlation between the uptake of the tracer and the macrophage infiltration ( 34 , 35 ). Other examples of PET include 68 Ga-DOTATATE PET ( 36 ), used in the expression of somatostatin receptor imaging, as the tool of detecting artery inflammation, or CD80-targeting PET Tracers ( 37 ).…”
Section: Imaging Identification Of Vulnerable Carotid Plaquementioning
confidence: 97%
“…In a multicenter prospective cohort study of patients with carotid stenosis and recent stroke/transient ischemic attack, Kelly et al showed that plaque inflammation associated 18 F-FDG uptake independently predicted future recurrent stroke after PET ( 33 ). Similarly, in a PET study using 18 F-fluorcholine ( 18 F-FCH), histological analysis of carotid endarterectomy specimens revealed a strong correlation between the uptake of the tracer and the macrophage infiltration ( 34 , 35 ). Other examples of PET include 68 Ga-DOTATATE PET ( 36 ), used in the expression of somatostatin receptor imaging, as the tool of detecting artery inflammation, or CD80-targeting PET Tracers ( 37 ).…”
Section: Imaging Identification Of Vulnerable Carotid Plaquementioning
confidence: 97%
“…The initiation of atherosclerosis depends on the accumulation of small lipoprotein particles in the intima, particularly at sites of hemodynamic strain, caused by the intake of diets high in cholesterol and saturated fats ( 1 , 7 , 8 ). These particles are susceptible to oxidative stress, which promotes the attraction of leukocytes, particularly phagocytes.…”
Section: Pathophysiology Of Vulnerable Plaquesmentioning
confidence: 99%
“…Atherosclerotic plaques are regarded as a gradual buildup of a heterogeneous collection of lipids, fibrous tissue, inflammatory cells, and other materials in the arterial wall. This process involves a series of specific cellular and molecular events in the arterial lesions, which can serve as local targeting epitopes for nanoparticles ( Shah, 2009 ; Magnus et al, 2019 ), including endothelial cell activation ( Andelovic et al, 2021 ), inflammation ( Soehnlein and Libby, 2021 ), angiogenesis ( Camaré et al, 2017 ), apoptosis ( van Tilborg et al, 2010 ), platelet activation, and thrombus ( Sanz and Fayad, 2008 ) ( Scheme 1 ).…”
Section: Key Processes In Atherosclerosis Developmentmentioning
confidence: 99%